Potential of vibrational spectroscopy and chemometric analysis for the detection of agrochemical residues in food - Villanueva López, Eudes (2023)
Organic agriculture is highly valued internationally as it results in significant economic gains for the value chains of various food products. Within the organic certification process, the identification of agrochemical residues in food is vital for screening production lots that come from organic and/or conventional crops. Currently, the analysis of agrochemical residues is performed with highly sophisticated techniques such as liquid chromatography (LC) and gas chromatography (GC) coupled to mass detectors (MS), these techniques are highly expensive and complex. The present review provides insights into how the combination of vibrational spectroscopy with appropriate chemometric techniques (multivariate statistics) can be used to develop methods for classification and quantification of agrochemical residues in various food matrices in a simple way, avoiding the use of toxic reagents, reducing operating costs and long analysis times in laboratories. The development of portable technology in vibrational spectroscopy would allow in-situ analysis in crop fields and agri-food industries.